2015
DOI: 10.3944/aott.2015.14.0035
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic stabilization of anterior shoulder instability using a single anterior portal

Abstract: Instability surgery performed using a single arthroscopic anterior portal provided findings comparable with the literature regarding clinical outcomes, postoperative shoulder movements and low recurrence rates, emphasizing the importance of appropriate patient selection rather than the number of the portals. The use of a single portal is less invasive and reduces the surgical period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
2
8
0
3
Order By: Relevance
“…Moreover, in some studies, much higher rates of postoperative recurrent shoulder dislocation have been reported. 7 In other studies, similar clinical results to those of open procedures have been reported. 13 , 14 Single anterior portal application that we perform at our clinic provides several advantages in this sense compared with double anterior portal, which has been the classic technique for surgical treatment of the shoulder for many years.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, in some studies, much higher rates of postoperative recurrent shoulder dislocation have been reported. 7 In other studies, similar clinical results to those of open procedures have been reported. 13 , 14 Single anterior portal application that we perform at our clinic provides several advantages in this sense compared with double anterior portal, which has been the classic technique for surgical treatment of the shoulder for many years.…”
Section: Discussionsupporting
confidence: 73%
“…Successful results observed in studies of anterior instability treatment using single anterior portal without the need for an additional portal have been published in literature. 6 , 7 …”
mentioning
confidence: 99%
“…These techniques rely on using as many anchors as possible to “spot weld” the detached anterior labrum to the glenoid. As a result more “spots” lead to stronger repair and less than 2 anchors can cause failure [5, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…[5, 6] The idea of using a single anchor and adapt the open vertical apical suture technique described by S. Copeland [7] in the form of “purse- string” technique was first described in 2006 by O. Levy [8] and was found to be at least as successful as multiple anchor techniques [9].…”
Section: Introductionmentioning
confidence: 99%
“…This also can be associated with lower patient morbidity. 3,[8][9][10] In sports medicine, we continue to try to provide improved outcomes by decreasing size and number of incisions, and in this technique we describe a single-incision anterior labrum repair without the need for a posterior incision. Our technique uses the NanoScope (Arthrex, Naples, FL) to eliminate the posterior portal, achieving a single-incision arthroscopic anterior labrum repair.…”
mentioning
confidence: 99%